Building frame- pile foundation-soil interactive analysis using 3D-FEM - Sawant, V.A.; Chore, H.S. (Journal of Structural Engineering, 2025)
The effect of the soil-structure interaction on a simple single storeyed and two bay space frame resting on a pile group embedded in cohesive soil (clay) with flexible cap is examined in this paper by resorting to a more rational approach and realistic assumptions based on three dimensional finite element analysis. Elements of superstructure and substructure are descretized using 20- noded isoparametric continuum elements while interface between the soil and pile is modeled using 16- noded isoparametric interface elements. Owing to viability in terms of computational resources and memory requirement, an approach of the uncoupled analysis is generally preferred to the coupled analysis of the system. However, a simple procedure is proposed for the interactive analysis of the system in which building frame and pile foundation is considered as a single compatible unit. The investigation considers the interaction between pile cap and underlying soil. In a parametric study conducted using the proposed procedure, effect of pile spacing in a pile group and configuration of the pile group is evaluated on the response of superstructure. The response of superstructure is considered in terms of displacement at top of the frame and moment in the superstructure columns. Effect of soil-structure interaction is found to be quite significant for the type of foundation used in the study with percentage increase in (i) displacement at top of the frame being in the range of 76-137%, (ii) maximum positive moment in superstructure columns being in the range of 13-15% and (iii) negative moment being in the range of 27-29%. Further, effect of thickness of pile cap is found prominent on top displacement but marginal on moment in columns. Moreover, a fair agreement is seen in the results obtained by using the proposed procedure and the results obtained by using uncoupled approach.